Benchmarking dalam Manajemen Sebuah Perpustakaan - Eke Wince (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This article is a theoretical study of the concept of benchmarking in library management to improve the quality of services and functions. The formulation of the problems raised is how the concept of benchmarking is and how its application to the existence and implementation of the functions of library institutions are. The method of writing in this article is to describe the concepts of benchmarking and then put the library activities on the concepts found. Benchmarking can and will be implemented in a library as a form of library development in a dynamic and sustainable way. Benchmarking done at this time tend to be external and functional. A library will apply benchmarking if its management system led to a total quality management system. It means that the empowerment of an organization's resources is developed maximally, professionally and proportionally. A library tends to benchmark, if it had a strategic planning to increase satisfaction both morally and materially.